Guidelines for Naming in Islam - Dr. Atiq Ullah; Dr. Abdul Haq (Journal of Religion and Society, 2025)
In Islam, giving a good name to a child is a religious responsibility of the parents, as a name becomes a part of a person’s identity and influences their personality. The Prophet Muhammad ﷺ not only encouraged meaningful and good names but also practically changed unsuitable names. The most beloved names to Allah are those that reflect servitude to Him, such as Abdullah and Abdur Rahman. Naming children after the prophets is also recommended. Names can have an impact on a person’s life, as demonstrated when the Prophet ﷺ offered to change the name “Huzn” (harshness) to “Sahl” (ease) and he loved to take good omens form positive names. Names that imply misfortune or negative meanings, such as Harb guaranteed success, like Barrah (pious) or Alflah (successful), are also discouraged. The Prophet ﷺ changed the names of several companions to more appropriate ones either to avoid bad omens or to prevent self-glorification. Naming children after angels or using the Prophet’s specific title Abul Qasim is debated among scholars. The majority agree that such prohibitions were specific to the Prophet’s lifetime to avoid confusion in addressing him. Islamic teachings emphasize that names should be good, truthful and dignified so that they positively influence a person’s character and are a source of respect in society. Keywords: Naming In Islam, Good Names, Bad Names, and Meanings of the Names